Image-Based Computational Hemodynamics Analysis of Systolic Obstruction in Hypertrophic Cardiomyopathy - Fumagalli, Ivan; Vitullo, Piermario; Vergara, Christian; Fedele, Marco; Corno, Antonio F.; Ippolito, Sonia; Scrofani, Roberto; Quarteroni, Alfio (Frontiers in Physiology, 2022)
Hypertrophic Cardiomyopathy (HCM) is a pathological condition characterized by an abnormal thickening of the myocardium. When affecting the medio-basal portion of the septum, it is named Hypertrophic Obstructive Cardiomyopathy (HOCM) because it induces a flow obstruction in the left ventricular outflow tract. In any type of HCM, the myocardial function can become compromised, possibly resulting in cardiac death. In this study, we investigated with computational analysis the hemodynamics of patients with different types of HCM. The aim was quantifying the effects of this pathology on the intraventricular blood flow and pressure gradients, and providing information potentially useful to guide the indication and the modality of the surgical treatment (septal myectomy). We employed an image-based computational approach, integrating fluid dynamics simulations with geometric and functional data, reconstructed from standard cardiac cine-MRI acquisitions. We showed that with our approach we can better understand the patho-physiological behavior of intraventricular blood flow dynamics due to the abnormal morphological and functional aspect of the left ventricle. The main results of our investigation are: a) a detailed patient-specific analysis of the blood velocity, pressure and stress distribution associated to HCM; b) a computational-based classification of patients affected by HCM that can complement the current clinical guidelines for the diagnosis and treatment of HOCM.